Revisiting of interest rate channel: Nonlinear transmission of monetary policy shocks to the Turkish economy - Durmuş Çağrı Yıldırım; Tugba Turan (Journal of Central Banking Theory and Practice, 2023)
This study examines the effectiveness of non-linear monetary policy interest rate channel shocks for the Turkish economy using the threshold VAR analysis in the period of 2006-2019. The interest channel is examined with the two models for both consumption transfer and investment transfer models. The results show that the interest rate channel is effective in the high regime (high macroeconomic instability) for the consumption transfer model, and it is partially effective in the low regime (low macroeconomic instability). On the other hand, for the model with investment expenditures flow, the interest rate channel is partially effective in both high and low regimes.This paper discusses the dynamics of bank regulation in the Sub-Saharan African (SSA) region during the period before the 1990s and post 1990s and describes the trends in bank regulatory measures between 1995 and 2017 using the updated databases of the World Bank's Bank Regulation and Supervision Surveys, Before the 1990s, bank regulation in the majority of SSA countries was inadequate and that led to multiple occurrences of banking crises, As a result, many countries introduced the financial sector reforms from the late 1980s that included major adjustments in the banking regulatory and supervisory frameworks, In both low-income and middle-income SSA economies, bank regulatory environment became more stringent over time, driven by increased restrictions on bank entry barriers and ownership structure, as well as the introduction of macroprudential policies in the case of the former, while in the case of the latter, it was influenced by more restrictions on bank ownership structure and capital regulation requirements, as well as the adoption of macroprudential policies, Overall, the bank regulatory environment was slightly more stringent in middle-income than in low-income SSA countries over the period under review.
Keywords: E43; E52; E58; C24; 330; Turkish Economy; Monetary Policy Shocks; Nonlinear transmission; Interest Rate Channel